PENGUJIAN KET AHANAN KOLEKSI GENOTIPE KEDELAI TERHADAP PENYAKIT BISUL BAKTERI - Dyah Kusuma Anggraini; Budi Tjahjono; Antonius Suwanto; Hajrial Aswidinnoor (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1995)
The objective of the research was to evaluate the resistance of soybean genotype in the germplasm collection to pustule disease. Seventy five genotypes were evaluated using spray inoculation method. Inoculation was done on the third week after planting. The 75 genotypes evaluated consists of 29 local varieties, 8 national varieties, 23 introduction, and 15 experimental lines. Results of the experiment showed that among the 75 genotypes tested, one local variety, Si Pinang was found resistant to the pustule disease (Xanthomonas campestris pv. glycines). The resistant local variety was collected from Langkat, North Sumatra.